University Election Analysis Logistic Regression Approach with Dummy and Ordinal Variables - Devni Prima Sari; Miftha Delinda (Mathematical Journal of Modelling and Forecasting, 2023)
Education has a very important role to advance the development of a country. One of them is the university. Thus, if you continue your studies at university, it is hoped that you will have the knowledge and skills in accordance with the study program you are taking, which will later become the basic capital to be more competent in the world of work. Logistic regression is a statistical method that can be used to determine the factors that influence the choice of university for class XII Phase F students. The dependent variable consists of two categories. This research aims to determine the factors that influence the choice of university for class XII Phase F students. This type of research is applied research and uses primary data obtained from filling out questionnaires. This research was carried out at SMAN 3 Padang. The population in this study were all students in class XII Phase F at SMA Negeri 3 Padang with a sample of 78 students obtained using the Purposive Sampling method. The results of the research show that the factors that influence the choice of university for class XII Phase F students at SMA Negeri 3 Padang are father's work based on educated and trained labor, father's work based on educated labor, father's work based on trained labor, father's work based on uneducated and unskilled labor, convenient university location, easy access to transportation, rent, food and daily living costs -affordable days according to budget, and information from social media and websites.